Improving assistive technology in practice: Contributions from interdisciplinary research and development and collaboration - Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika; da Silva, Sara Raquel Martins [UNESP]; Rodrigues, Ana Cláudia Tavares (My University, 2018)
This paper describes a collaborative strategy shared by a rehabilitation center and a public usniversity with a goal to improve the knowledge on assistive technology and rehabilitation research and development in Brazil. Here, we focus on the contributions, challenges and investigations performed so far.
Keywords: Assistive technologies; Design; Interdisciplinary; Rehabilitation